Evaluating social media participation for successful marketing and communication by selected private game reserves, Eastern Cape, South Africa - Booth, Tara (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
Social media has become one of the defining features of the technological advances known as Web 2.0. As social media has increased in popularity, so businesses are expected to participate. Social media platforms enable businesses to widely broadcast a message as well as interact directly with individual customers. Customers are also able to interact directly with one another and share information and reviews about products and services offered. This suits the tourism industry particularly well. Internationally, research has shown that individuals use social media and other online tools to research potential holiday destinations. In addition social media is used during travel to share snapshots and commentary as well as after travel, through reviews and recommendations on platforms such as TripAdvisor. However, few studies have investigated how tourism destinations use social media to attract new clients and retain existing clients. Very little research has been done on tourism and social media in South Africa despite the importance of this industry to Gross Domestic Product (GDP). This study focused on four-star establishments within the photographic wildlife tourism industry in the Eastern Cape of South Africa. An initial survey of social media participation was carried out within the framework set out by Chan and Guillet (2011); this was then followed up with interviews with selected managers. Results showed that, in general, Private Game Reserves (PGRs) had embraced social media as a communication and marketing platform; despite concerns raised about the lack of control over content as well as poor understanding of the influence social media might have on the bottom line. TripAdvisor, Facebook and Twitter were the most commonly used platforms due to management familiarity with the platform and their ease of use. Few lodges utilised blogs or content sites such as YouTube and management cited time commitments associated with this type of platform as a reason for non-participation. However, although most PGRs or lodges had a profile on social media, this did not always mean active participation. Frequently, lodges began updating but gradually stopped after a few months. It was noted however that only one of the lodges interviewed retained an individual whose sole responsibility was social media; generally lodges did not feel that a dedicated person was necessary. This may result in a lack of time available on the part of the individual responsible or simply be a case of not understanding the platform or how to use it effectively. However, none of the PGRs with poor social media participation responded to interview requests and therefore it was not possible to determine the reasons for their poor participation. Among those lodges that actively participated, most succeed in retaining fans and followers through consistent posting of relevant and interesting content as well as customised responses that encouraged fans or followers' interaction. However, there did not appear to be any evidence of using social media to learn about fans and followers in order to better customise the lodge offerings. This may not be necessary in this type of industry as PGRs sell a specific product and have a limited ability to customise offerings. In addition, there may be other sources of market information which lodges prefer to use. Special offers, competitions and promotions had limited success on social media. Generally, lodges used social media to promote links to a dedicated competition or promotions page. In conclusion, the managers interviewed felt strongly that social media had made a measureable impact on the tourism industry and was a channel that was here to stay. Further research around the best practice and most effective use will enable PGRs to develop and maintain effective strategies for social media participation.
Keywords: Social media -- Economic aspects; Online social networks -- Economic aspects; Game reserves -- South Africa -- Eastern Cape -- Marketing; Internet marketing -- Economic aspects; Social media -- Marketing; Tourism -- Marketing; Communication in management